Psoriasis and uveitis: links and risks - Fotiadou C (Dove Medical Press, 2019)
Christina Fotiadou, Elizabeth LazaridouSecond Department of Dermatology-Venereology, Aristotle University Medical School, Thessaloniki, GreeceCorrespondence: Christina FotiadouSecond Department of Dermatology-Venereology, Aristotle University Medical School, 1 Chrysochoou Street 1221, Larisa, GreeceTel +30 697 728 0180Email christinafotiadou@yahoo.comAbstract: Uveitis, an inflammatory disorder of the mid-portion of the eye, is considered a relatively rare but very serious ocular complication of psoriasis. Data on the specific characteristics of uveitis in the background of psoriasis are extremely limited. The presence of uveitis in the context of psoriasis has been estimated to occur in 7–20% of the psoriasis cases. This incidence tends to be higher in patients suffering from psoriasis and psoriatic arthritis (PsA) or PSA alone. Psoriatic uveitis is usually bilateral, chronic, and severe. In term of pathogenesis, both psoriasis and uveitis are considered as paradigms of T-helper 1/T-helper 17 (Th1/Th17) inflammatory reactions. Certain cytokines such as tumor necrosis factor-α (TNF- α), Interleukin-17 (IL-17), IL-23, and IL-6 play a significant role in the pathogenesis of both psoriasis and uveitis. As uveitis shares common pathogenetic mechanisms with psoriasis in certain circumstances, both diseases may benefit from the same targeted biologic therapies. Undiagnosed and under-treated cases of psoriatic uveitis may cause significant morbidity and even vision loss. Larger prospective studies are needed in order to further investigate the association between these two entities.Keywords: psoriasis, uveitis, pathogenetic link